PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Genta Al Rizky Yusuf (2021)
This research aims to determine the effect of good corporate governance on firm value with financial performance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019 period. This research is a type of quantitative research that uses a sample of 155 manufacturing companies. Techniques to analyze the data in this research used classical assumption test, multiple linear regression, path analysis, and hypothesis testing with t test and coefficient of determination test. Based on the results of the previous data analysis, it can be concluded that (1) institutional ownership has no significant effect on firm value, (2) the audit committee has a significant positive effect on firm value, (3) institutional ownership has a significant effect on financial performance, (4) the audit committee has no significant effect on financial performance, (5) financial performance has a significant positive effect on firm value, (6) institutional ownership has a significant positive effect on firm value through financial performance, (7) audit committee has a significant positive effect on firm value through financial performance. Keywords : Institutional Ownership, Audit Committee, Financial Performance, and Company Value